1980
DOI: 10.1111/j.2044-8279.1980.tb00812.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Personal Lecture Notes and Teacher‐notes on Recall of University Students

Abstract: Two experiments studied the effects of note-taking, strategy of note-taking (short/long notes) and reviewing personal notes and/or simplified teacher-notes on immediate and delayed recall. One hundred and sixty university students, classified as either short or long note-takers, served as subjects. They listened to a recorded lecture and then their immediate and delayed retention was assessed by means of the free recall test. Analysis of results revealed that the act of note-taking has facilitative effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 4 publications
1
17
0
Order By: Relevance
“…Reviewing provided notes did produce higher achievement than reviewing personal notes when the review period lasted for 30 minutes and when the provided notes were of sufficient detail (Maqsud, 1980). Maqsud emphasized the importance of detailed notes, speculating that such notes are best for reviewing knowledge acquired during the lecture and for additionally supplying "new" lecture information originally overlooked or misunderstood.…”
Section: Providing Notes For Reviewmentioning
confidence: 98%
“…Reviewing provided notes did produce higher achievement than reviewing personal notes when the review period lasted for 30 minutes and when the provided notes were of sufficient detail (Maqsud, 1980). Maqsud emphasized the importance of detailed notes, speculating that such notes are best for reviewing knowledge acquired during the lecture and for additionally supplying "new" lecture information originally overlooked or misunderstood.…”
Section: Providing Notes For Reviewmentioning
confidence: 98%
“…While this area awaits investigation, related research has been conducted on the efficacy of providing students with lecture notes prepared by the instructor (see Kiewra, 1984cKiewra, , 1985d. Findings indicate that students who listen to a lecture and review the instructor's notes generally achieve more than do students who take and review their own notes (e.g., Fisher and Harris, 1973;Kiewra, , 1985bKiewra and Benton, 1985a;K.iewra and Frank, in press;Maqsud, 1980) and that notetakers who review both sets of notes generally achieve most of all (Annis and Davis, 1975;Maqsud, 1980;Thomas, 1978). Kiewra (1985d) speculates that the inslructor's notes produce relatively higher achievement because they are often more complete than students' personal transcriptions and therefore provide a better means of external storage.…”
Section: Absenteeismmentioning
confidence: 99%
“…The facility to review the material actually provided by the lecturer is important for some students; it has been found that students given handouts scored better on recall than those who only took their own notes (Maqsud, 1980). It has also been shown that students make errors when copying from overheads during lectures (Mahalski, 1995), so the availability on the computer of all the overheads used by the lecturer is also important.…”
Section: Revisionmentioning
confidence: 99%